Proceedings (105) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Cassava flour and starch: progress in research and development edited by D Dufour, G M O'Brien, Rupert Best 409pp